2012
DOI: 10.1111/j.1440-6055.2011.00853.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and molecular phylogenetics of the cryptic species of the Gonipterus scutellatus complex (Coleoptera: Curculionidae: Gonipterini)

Abstract: The Eucalyptus Weevil, generally referred to as Gonipterus scutellatus Gyllenhal, 1833 is a significant pest of Eucalyptus species in Africa, America, Europe and New Zealand. It has recently become a pest of Eucalyptus globulus plantations in Western Australia, despite the presence there of the mymarid egg‐parasitoid Anaphes nitens (Girault). Recent taxonomic study has indicated G. scutellatus to comprise a complex of cryptic species, obscuring the identity of the various pest populations of the weevil in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
168
2
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(215 citation statements)
references
References 41 publications
3
168
2
11
Order By: Relevance
“…Gonipterus scutellatus was thought to have spread globally (except Asia), but it was later discovered that the species had been misidentified and that 'G. scutellatus' represents a complex of at least three species (Mapondera et al 2012). These include G. platensis found in New Zealand, South and North America and western Europe, G. pulverulentus in South America, and an undescribed species (Gonipterus sp.…”
Section: Changing Patterns Of Pest Invasionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gonipterus scutellatus was thought to have spread globally (except Asia), but it was later discovered that the species had been misidentified and that 'G. scutellatus' represents a complex of at least three species (Mapondera et al 2012). These include G. platensis found in New Zealand, South and North America and western Europe, G. pulverulentus in South America, and an undescribed species (Gonipterus sp.…”
Section: Changing Patterns Of Pest Invasionmentioning
confidence: 99%
“…plicatuloides detected in South Africa in 2014 (Samantha Bush, unpublished). In addition, Nahrung and Swain (2015) listed the Gonipterus scutellatus complex and not the three Gonipterus species as described by Mapondera et al (2012). These changes have been included in Table 1, which lists a total of 42 pest introductions.…”
Section: Changing Patterns Of Pest Invasionmentioning
confidence: 99%
“…This is the case of G. pulverulentus, which had been previously misidentified in eastern South America as Gonipterus gibberus Gyllenhal, 1833. In New Zealand, America, and Western Europe, it was found that the reported pest species was actually G. platensis, instead of G. scutellatus (Mapondera et al, 2012); both species were dispersed with the host plant (eucalyptus).…”
Section: Introduced Non-quarantine Pests Eucalyptusmentioning
confidence: 99%
“…to eucalyptus plantations was first noticed when a large number of this species was found in E. globulus plantations in Australia (Mapondera et al, 2012). The introduction of E. globulus from the Tasmanian region in many parts of the world may have been responsible for the entry of the pest in South America (Mapondera et al, 2012).…”
Section: Introduced Non-quarantine Pests Eucalyptusmentioning
confidence: 99%
See 1 more Smart Citation